2020
DOI: 10.1002/jgm.3162
|View full text |Cite
|
Sign up to set email alerts
|

LINC01410 promotes cell proliferation and migration of cholangiocarcinoma through modulating miR‐124‐3p/SMAD5 axis

Abstract: Background: Cholangiocarcinoma (CCA) is generally associated with high incidence and poor prognosis. Nowadays, increasing experimental data demonstrate that long non-coding RNA (lncRNA) plays an indispensable role in tumor occurrence.Nevertheless, the specific mechanism of lncRNA is not clear in CCA. Methods:The relative expressions of lncRNAs, miRNAs, and mRNAs were detected by real-time quantitative PCR (RT-qPCR). CCK8 and colony formation assays were applied to examine cell proliferation ability in CCA. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Knockdown of LINC01410 attenuates cell growth and arrests cell cycle at G0/G1 phase via suppressing miR‐3128 in colon cancer 11 . LINC01410 serves as an oncogenic that accelerates cholangiocarcinoma tumorigenesis by modulating the expression of SMAD5 via directly targeting miR‐124‐3p 12 . In this study, LINC01410 knockdown restrained cell proliferation and colony formation ability, and arrested cell cycle, and accelerates cell apoptosis, suggesting that LINC01410 plays pivotal roles in the modulation of NBL progression in vitro.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Knockdown of LINC01410 attenuates cell growth and arrests cell cycle at G0/G1 phase via suppressing miR‐3128 in colon cancer 11 . LINC01410 serves as an oncogenic that accelerates cholangiocarcinoma tumorigenesis by modulating the expression of SMAD5 via directly targeting miR‐124‐3p 12 . In this study, LINC01410 knockdown restrained cell proliferation and colony formation ability, and arrested cell cycle, and accelerates cell apoptosis, suggesting that LINC01410 plays pivotal roles in the modulation of NBL progression in vitro.…”
Section: Discussionsupporting
confidence: 49%
“…Here, the LINC01410 expression was markedly enhanced in NBL tissues and cells. Notably, LINC01410 is high‐expressed in diverse tumors, including gastric cancer, 13 cervical cancer, 33 and cholangiocarcinoma 12 . In this study, high LINC01410 expression was positively associated with WHO grade in NBL patients, and conferred a survival disadvantage to NBL patients.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Studies from different groups have confirmed that the dysregulation of lncRNA expression is closely related to the biological behavior of CCA cells. Upregulation of these lncRNAs, including KCNQ1OT1 [48], LMCD1-AS1 [37], TP73-AS1 [22], SNHG1 [49], SOX2-OT [39], LINC01410 [50], ASAP1-IT1 [51], DANCR [52], FLVCR1-AS1 [53], NNT-AS1 [54], RMRP [55], CCAT2 [56], HOTAIR [57], LINC01296 [58], LOXL1-AS1 [59], NEAT1 [60], PVT1 [43], HEIH [61], LINC01061 [62], may promote the migration and invasion of CCA cells, . On the other hand, the downregulation of several lncRNAs plays the same role in CCA cells including LINC01714 [63], FENDRR [64], MEG3 [65], and MIR22HG [66].…”
Section: Promotion Of the Migration And Invasion Of Cca Cellsmentioning
confidence: 99%
“…LINC01410 is a lncRNA highly expressed in pancreatic cancer tissues and cell lines [52]. High expression in cholangiocarcinoma and gastric cancer patients have been associated with poor prognosis and survival [53,54]. These lncRNAs may be facilitating the promotion of tumor progression, proliferation and invasion which might have impacted the survival of patients in the short survival group.…”
Section: Upregulated Genesmentioning
confidence: 99%